Border policies and migrant deaths at the Turkish-Greek border. (May 2019) - Ulusoy, Orçun; Baldwin-Edwards, Martin; Last, Tamara
Abstract: This paper investigates the impact of developments in Turkish migration management policy and changes in management of the Greek-Turkish border on border deaths prior to the 2015 mass inflow of refugees. As the locus of multiple and sustained Frontex operations, as well as several autonomous major changes in relevant policies and practices over the 2000–2014 period, the Greek-Turkish border can serve as a post hoc laboratory for analyzing the implications of EU-influenced migration and border management for deaths on the border. We conclude that a chaotic mix of national politics, policy development and law enforcement practices, flexible smuggling networks, and Frontex operations contributed to the mass inflows of 2015–2016 and ensured mass casualties.